If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2m + -10) = 2m + 10 Reorder the terms: 3(-10 + 2m) = 2m + 10 (-10 * 3 + 2m * 3) = 2m + 10 (-30 + 6m) = 2m + 10 Reorder the terms: -30 + 6m = 10 + 2m Solving -30 + 6m = 10 + 2m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-2m' to each side of the equation. -30 + 6m + -2m = 10 + 2m + -2m Combine like terms: 6m + -2m = 4m -30 + 4m = 10 + 2m + -2m Combine like terms: 2m + -2m = 0 -30 + 4m = 10 + 0 -30 + 4m = 10 Add '30' to each side of the equation. -30 + 30 + 4m = 10 + 30 Combine like terms: -30 + 30 = 0 0 + 4m = 10 + 30 4m = 10 + 30 Combine like terms: 10 + 30 = 40 4m = 40 Divide each side by '4'. m = 10 Simplifying m = 10
| 20=14m-9+3(5m) | | 17-x=3x-7 | | 8x-6=-2(6x+4)+2x | | x^5-4x^4+x^3+2=0 | | 47+3=40 | | X=45 | | y=4-xsqaured | | 16y^2+28=0 | | 10x+11y= | | x^4+5x^2+49=0 | | -(-x-5)+5(x-9)=2(x+8)-2x+5 | | 3n+2=9 | | 2x=3(1-x)-(x-1) | | 2x^3-12x^2+24x-2=0 | | 3x-(x-2)=(2x-1)(-3x+9) | | (2x-1)(-3x+9)=0 | | 2(c-2)whenc=7 | | 3x-1=4(2x-5) | | 63-4x=5x+23 | | 0.4(3k-0.6)= | | 13-9x=73-23x | | 0.05x-.6=5.3 | | 5p-6+3p=12 | | 13h+6d-9d-7h=0 | | (4x-37).12=276 | | 3(d-8)-6=9(d+2) | | -17-4x=-7-7x | | x^2+2y^2=1 | | 0.5(8+2)=17 | | 11=-4(x+1) | | f=35r^2 | | 3*x-5=34 |